Potential effects of brown howler monkey extinction on dispersal services in fragmented forests void of large dispersers - Natani, Thays; Culot, Laurence [UNESP]; da Cunha, Rogério Grassetto Teixeira (Springer Nature, 2024)
The dispersal of large-seeded species strongly depends on medium-sized and large frugivores, such as primates, which are highly susceptible to population declines. In the Atlantic Forest, brown howler monkeys Alouatta guariba are medium-sized folivorous-frugivorous species that are likely to occur in small to large fragments where the largest frugivores are extinct. However, populations of this primate have been suffering from forest fragmentation, habitat loss, hunting, and the direct and indirect effects of yellow fever outbreaks, which increase the importance of understanding their role as seed dispersers and the impacts of their potential loss. The richness and abundance of large-seeded species might also be reduced in smaller fragments, which could directly affect the magnitude of the potential impact of disperser extinction on plant recruitment. Here, we tested the following mutually exclusive predictions on the effect of fragment size on plant richness and relative density of medium- and large-seeded species consumed by brown howler monkeys in fragments smaller than 1500 ha: the number and the relative density of plant species potentially affected by the local extinction of these monkeys will be (1) directly related to forest fragment size, or (2) not related to forest fragment size. Plant richness and the relative density of large- and medium-sized seed species consumed by brown howler monkeys did not vary with fragment size, corroborating our second prediction. Thus, the local extinction of brown howler monkeys would have a similar potentially negative impact on plant regeneration for the range of tested fragment sizes. We discuss the limitations of our results and suggest other lines of enquiry for the refinement of our conclusions.
Keywords: Alouatta guariba; Conservation; Ecological interactions; Forest fragmentation